A Different Nested Logit Model Structure Consistent with Random Utility Theory for Various Freight Types - A Case Study for Istanbul - Aksoy, Berna; Gursoy, Mustafa (SVEUCILISTE U ZAGREBU, FAKULTET PROMETNIH ZNANOSTI, 2023)
Freight transport significantly contributes to urban traffic but is often overlooked by decisionmakers compared to passenger transport. Conventional transportation modelling studies often use aggregate approaches for freight transport, undoubtedly due to the difficulty of data collection. However, the nature of freight transportation is much more complex. For this reason, examining the determinants of freight vehicle preferences with discrete approaches is crucial for the contributions that can be put forward, especially in local studies. To address this apparent gap in the study of local disaggregated approaches to freight transport, we present a discrete modelling -based methodology to investigate the factors that determine freight vehicle preferences for shippers and senders. The estimated nested logit model is constructed with the RU2 approach, the second part of random utility theory, thus avoiding the theoretical inconsistencies that arise when generic coefficients are used. As a result, the model structures provided satisfactory results compared to the literature. It was revealed that the factors affecting freight vehicle choice preferences were influenced by packaging preferences and differed according to freight groups. This local study is the first nested logit study for freight modelling in Istanbul and it is aimed to shed light on future national studies.
Keywords: transportation modelling; freight modelling; random utility theory; discrete choice; logit models; nested logit; TRANSPORT; CHOICE; Transportation